Implementasi Game Theory Dalam Penentuan Strategi Bersaing Pada Produk Sepeda Motor - Wahyudi, Ahmad; Sari, Rina Widya; Harleni, Silvia (Universitas Cokroaminoto Palopo, 2024)
Competition in the business world, especially land transportation equipment, is currently getting tighter with its use in people's lives, one of which is motorbikes. Its use is very easy and very helpful in everyday life, causing many people to be interested in it. This research aims to determine competitive strategies in motorbike product competition by applying mathematical methods, namely Game Theory. The research results obtained show competition between Honda motorbike products and Yamaha motorbike products with Honda's optimal strategy being product quality, while the optimal strategy for Yamaha motorbike products to compete with Honda motorbike products is model and spare parts.